Specific aspects of vertical roller mills design selection - Klymenko, Mykola; Marach, Vasyl (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article analyzes specific design selection aspects of vertical roller mills, essential for grinding materials like granulated slag in the cement and mining industries. The research focuses on improving mill’s working elements to enhance efficiency, reduce energy consumption, and increase wear resistance under harsh operating conditions. Modern innovative designs, including multi-roller and modular concepts with active redundancy, are reviewed for improved reliability. The comminution principle relies on energy-efficient compression and shear within the material bed. A comparative analysis of various mills configurations, differing in roller and table geometry, is presented, demonstrating how design adaptations such as specialized rollers for high-moisture slag optimize performance, wear rate, and energy efficiency.
Keywords: vertical roller mills; granulated slag; structural elements; mill capacity